A rehabilitation programme for people with multimorbidity versus usual care: A pilot randomized controlled trial. Issue 1 (19th July 2018) - Barker, Kathryn; Holland, Anne E; Lee, Annemarie L; Ritchie, Kathryn; Boote, Claire; Lowe, Stephanie; Pazsa, Fiona; Thomas, Lee; Turczyniak, Monica; Skinner, Elizabeth H
Background: Multimorbidity, the coexistence of two or more chronic conditions, is common in clinical practice. Rehabilitation for people with multimorbidity may provide access to a rehabilitation programme that can address common symptoms and risk factors for multiple chronic diseases. Objective: The aims of this study were to (1) evaluate the feasibility of a rehabilitation programme compared to usual medical care (UMC) in people with multimorbidity and (2) gather preliminary data regarding clinical effects and impact on functional exercise capacity, activities of daily living, health-related quality of life and resource utilization. Design: A pilot feasibility parallel randomized controlled trial was undertaken. Adults with multimorbidity were randomized to the rehabilitation programme (intervention) or UMC (control). The duration of the rehabilitation programme was 8 weeks and comprised exercise (1 h, twice weekly) and education (1 h, once weekly). The UMC group did not participate in a structured exercise programme. Results: One hundred people were screened to recruit 16 participants, with a 71% completion rate for the intervention group. The rehabilitation group achieved a mean (standard deviation) improvement in 6-minute walk distance of 44 (41) m and the UMC group of 23 (29) m. Conclusions: This study suggests that it would be feasible to conduct a larger randomized control trial investigating a rehabilitation programme for people with multimorbidity. Low uptake of the study suggests that refinement of the inclusion criteria, recruitment sources and programme model will be needed to achieve the number of participants required.